Accidental or intentional exposure to potentially toxic medications, natural toxins and chemicals during pregnancy: analysis of data from Tox Info Suisse (Swiss Medical Weekly, 2018)
OBJECTIVE Affected women and health professionals are still often unsure about how to react to exposures to potentially harmful agents during pregnancy. We wanted to find out which agents worry both pregnant women and professionals, under what circumstances the exposures take place, how they are currently dealt with and how serious they are. METHODS Making use of the archives of Tox Info Suisse, the foundation that provides poisons information in Switzerland both for members of the general public and for healthcare professionals, we set up an analysis of exposures to possibly harmful agents during pregnancy. Queries during pregnancy between 1995 and 2015 were analysed. Demographic information, exposure and agent characteristics as well as – in a subgroup of cases – the corresponding treatments were considered in the present descriptive, retrospective analysis. RESULTS Over the 21-year period, 2871 exposures during pregnancy were identified. The majority of the calls were made by members of the general public (2035, 70.9%; most often by the affected women themselves), followed by physicians (733, 25.5%). General public queries were mostly due to exposures connected with household chemicals (675/2035, 33.2%); those of physicians were most often due to medications (415/733, 56.6%). The majority of agent exposures occurred accidentally at home, at work, outdoors or at various other places (2297/2871, 80.0%). Less frequently, the exposures were intentional and had a suicidal, abusive, criminal or other character (471/2871, 16.4%). Of the 2871 calls, 905 cases with symptoms were recorded. Of the 1268 symptoms, 820 were mild (64.7%), 144 moderate (11.3%), 24 severe (1.9%, including 12 abortions) and 280 were not further specified (22.1%). In 1867 cases (65%), a total of 2331 measures were recommended by Tox Info Suisse, 1961 thereof to be carried out immediately. The two most common immediate measures were exposure interruption (412/1961, 21.0%) and forwarding to another institution (345/1961, 17.6%). In 70 cases, physicians’ follow-up reports could be analysed; paracetamol was the agent most frequently involved (15 cases), followed by mefenamic acid (9) and the household product sodium hypochlorite (9). CONCLUSIONS Tox Info Suisse recorded an average of 137 cases of agent exposure during pregnancy per year, mostly due to accidents with household products. Suicidal intentions played a role in a considerable number of exposures. Measures are needed to prevent accidental exposure of pregnant women to toxic substances and to support them in this exceptional life period.